2003
DOI: 10.1097/00004872-200310000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-activated K+ channels mediate relaxation of forearm veins in chronic renal failure

Abstract: The results demonstrate that the endothelium-dependent relaxation in forearm veins from controls and non-dialysed patients is mediated by release of nitric oxide and EDHF. In contrast, the relaxation in veins from dialysed patients is mediated mainly by EDHF. EDHF-induced relaxation involves activation of large-conductance Ca2+-activated K+ channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 45 publications
5
23
1
Order By: Relevance
“…Mullen et al (20) showed that the FMD response to hand warming is not attenuated by N-monomethyl-l-arginine, cyclooxygenase inhibition, or local autonomic nervous blockade. In patients who were on dialysis, vein relaxation was inhibited by tetraethylammonium chloride (inhibitor of Ca 2ϩ -activated K ϩ channels) but not N-monomethyll-arginine or asymmetrical dimethylarginine (43). In our study, serum 25(OH)D 3 and 1,25(OH) 2 D 3 levels were age-and SBP-independently and positively associated with FMD (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 44%
“…Mullen et al (20) showed that the FMD response to hand warming is not attenuated by N-monomethyl-l-arginine, cyclooxygenase inhibition, or local autonomic nervous blockade. In patients who were on dialysis, vein relaxation was inhibited by tetraethylammonium chloride (inhibitor of Ca 2ϩ -activated K ϩ channels) but not N-monomethyll-arginine or asymmetrical dimethylarginine (43). In our study, serum 25(OH)D 3 and 1,25(OH) 2 D 3 levels were age-and SBP-independently and positively associated with FMD (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 44%
“…Endothelial responsiveness was inhibited by calcium gated potassium channel blockade but not by inhibitors of NOS (ie, N G -monomethyl-L-aginine [L-NMMA] or ADMA). 19 Thus, substances other than inhibitors of NOS appear to be primarily responsible for the profound attenuation of EDV in ESRD patients.…”
mentioning
confidence: 99%
“…Collectively, these results indicate that in MSVs, vasodilation induced by BK is mediated in part by prostacyclin and NO, and NO at intermediate and high TMPs, respectively. The dilator response to BK, which persisted in the presence of L -NNA and indomethacin, may be attributable to EDHF [19,22]. …”
Section: Discussionmentioning
confidence: 99%
“…The VSM BK Ca and endothelial cell SK Ca channels have been suggested to mediate endothelium-dependent vasodilation in several vascular preparations [19,22], but whether these ion channels are involved in BK-induced dilations of MSV has not previously been reported. To investigate the effects of BK Ca and SK Ca channels in mediating vasodilation responses to BK, MSVs were individually treated with paxilline and apamin, which significantly reduced the maximum dilation in response to BK by 41.9 ± 5.7 and 47.9 ± 2.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation